CORPORATE PERFORMANCE MEASUREMENT BASED ON SUSTAINABILITY BALANCED SCORECARD AT PT INDOFOOD CBP SUKSES MAKMUR Tbk. FOR THE PERIOD 2022-2024 - Wilujeng, Amalia Azizah; Gunawan Putri, Alvianita; Widiarto, Ardian (Politeknik Negeri Semarang, 2026)
Sustainability issues and environmental responsibility have become important concerns for manufacturing companies. Although PT Indofood CBP Sukses Makmur Tbk. has expressed its sustainability commitment in its official reports, there have been media reports regarding alleged environmental issues, indicating a potential gap between commitment and actual implementation. This study aims to analyze the performance of PT Indofood CBP Sukses Makmur Tbk. for the period 2022–2024 using the Sustainability Balanced Scorecard method. This research employs a descriptive qualitative approach using secondary data derived from the company’s annual reports and sustainability reports. The analysis is conducted by comparing performance measurement results based on four and five perspectives. The results show that the company’s performance falls into the “Very Healthy” category based on four perspectives; however, the score declines after incorporating the environmental perspective, although it remains within the same category. This decline is caused by the low performance of environmental indicators, particularly energy intensity, greenhouse gas emission intensity, and water usage intensity. The inclusion of the environmental perspective provides a more comprehensive evaluation of the company’s sustainability performance.